The role of anticipation and neuroticism in developmental stuttering - Palombo, Francesco; Del Gado, Francesca; Rugolo, Francesca; Lasaponara, Stefano; Busan, Pierpaolo; Tomaiuoli, Donatella; Conversi, David (Frontiers in Psychology, 2025)
PurposePeople Who Stutter (PWS) are often characterized by the presence of cognitive-emotional issues, resulting in conditions such as social phobia and avoidance behaviors. Emotions have been demonstrated to have a role in modulating speech-motor systems. Thus, in PWS, emotion and cognition (i.e., higher levels of trait-stable-neuroticism-and contextual-anticipation-anxiety) could negatively influence speech-motor networks, resulting in an increased number of dysfluencies.MethodsTo test this hypothesis, we recruited 13 PWS who were matched to 13 Fluent Speakers (FS). Participants were all Italian speakers and completed the NEO-PI-3 scale to assess neuroticism, and the ASI-3 scale for anxiety sensitivity. Successively, participants considered 55 words (repeated two times) and 55 sentences, and completed a task in which they had to evaluate their anticipation of stuttering before reading them aloud. Anticipation scores, reading times, and frequency of stuttering were evaluated and used for analyses.ResultsFindings suggest that PWS mainly had higher social concern than the fluent speakers. Moreover, a tendency toward higher levels of neuroticism is evident. Linear regressions suggest that reading times in PWS (positively related to frequency of stuttering) may be mainly explained by stuttering anticipation scores and, secondarily, by neuroticism levels. Stuttering anticipation was also positively related to the recorded frequencies of dysfluencies.ConclusionStuttering anticipation and neuroticism may be useful indexes for predicting dysfluencies and speech behavior, in PWS. Surely, this may be related to long-life stuttering and adaptive/maladaptive compensation attempts. In every case, in a clinical context, this also suggests the importance of fully evaluating behavioral/emotional aspects of stuttering, to obtain a more complete picture of patients’ needs and “tailored”/multidisciplinary interventions.